Pengaruh Senam Kaki terhadap Nilai Ankle Brachial Index Pada Pasien Diebetes Melitus Tipe II: Sebuah Tinjauan Sistematis - Yofa Anggriani Utama; Sutrisari Sabrina Nainggolan (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Diabetes mellitus is a chronic disease that occurs due to metabolic disorders characterized by blood sugar levels that exceed normal limits. Diabetic foot is a complication of diabetes mellitus that can cause ulcers, infection, gangrene and charcot's atrophy. Diabetic foot exercise is one of the interventions that can overcome peripheral circulation problems that occur in type 2 diabetes mellitus patients.The purpose of this study is to identify the effect of diabetic foot exercise on the value of the ankle brachial index in Type II Diabetes Mellitus patients through a systematic review. The research design included in this systematic review uses a research design that is a quantitative method with a systematic review approach. The first article shows that the treatment group experienced an increase in mean and the control group experienced a decrease in the mean. The physical activity of the respondents affected the ABI value just before the ABI examination was carried out, and it was also influenced by cholesterol which the researchers did not control for all respondents. So it can be concluded that the diabetes foot exercise intervention has an effect in increasing blood circulation to the feet. The second article shows that when compared to the results of the ABI values for the two groups there are significant results, so that diabetic foot exercises can be given four times a week for one month, providing good benefits in increasing blood pressure in the legs. The results of this systematic review indicate that foot exercise has a good effect on ankle brachial index in type 2 diabetes mellitus patients who have problems with peripheral perfusion. If this intervention is given as often as possible, it will have a good effect on the range of motion of the joints so that it can improve the quality of life of patients with type 2 diabetes mellitus.